Scientific Rationale for a Bottom-Up Approach to Target the Host Response in Order to Try and Reduce the Numbers Presenting With Adult Respiratory Distress Syndrome Associated With COVID-19. Is There a Role for Statins and COX-2 Inhibitors in the Prevention and Early Treatment of the Disease? - Verrall, Geoffrey Mark (Frontiers in Immunology, 2020)
The inflammatory response to and the subsequent development of Adult Respiratory Distress Syndrome (ARDS) is considered to underpin COVID-19 pathogenesis. With a developing world catastrophe, we need to examine our known therapeutic stocks, to assess suitability for prevention and/or treatment of this pro-inflammatory virus. Analyzing commonly available and inexpensive immunomodulatory and anti-inflammatory medications to assess their possible effectiveness in improving the host response to COVID-19, this paper recommends the following: (1) optimize current health—cease (reduce) smoking, ensure adequate hypertension and diabetes control, continue exercising; (2) start on an HMG CoA reductase inhibitor “statin” for its immunomodulatory and anti-inflammatory properties, which may reduce the mortality associated with ARDS; and (3) consider using Diclofenac (or other COX-2 inhibition medications) for its anti-inflammatory and virus toxicity properties. For purposes of effectiveness, this needs to be in the early course of the disease (post infection and/or symptom presentation) and given in a high dose. The downsides to these recommended interventions are considered manageable at this stage of the pandemic.